Storage stability and quality of polyunsaturated fatty acid rich oil fraction from longtail tuna (thunnus tonggol) head using supercritical extraction - Ferdosh, Sahena; Sarker, Md. Zaidul Islam; Nik Abdul Rahman, Nik Norulaini; Jinap, Selamat; Haque, Akanda Mohamed Jahurul; Mohd Omar, A.K. (Taylor & Francis Online, 2014)
The polyunsaturated fatty acids (PUFA)-rich fish oil fractionated from tuna head using supercritical carbon dioxide (SC-CO2) were stored at 4°C and –18°C for 60 days to study the storage stability. The changes in fatty acids, iodine value (IV), peroxide value (PV), acid value (AV), and saponification value (SV) up to 30 days were found to be negligible, then started to decrease from 45 and the significant changes were observed at 60 days. At 4°C, the PV, AV, and SV were increased from 1.74 to 6.72 meq O2/kg oil, 1.36 to 5.56 mg KOH/g oil, and 182.73 to 190.74 mg KOH/g oil, respectively, while IV and PUFA were decreased from 185.43 to 175.35 g I/100 g oil and 43.07 to 33.94% at 60 days. It is concluded that SC-CO2 extracted PUFA-rich fraction could be maintained in good quality for consumption at both temperature up to 60 days.